The local impact and multiplier effect of universities in Lower Saxony on the labour market - Britta Stöver (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
This paper quantifies and compares the direct and indirect effects of labour demand generated by each university location in Lower Saxony. The results are classified in order to identify regional patterns. The applied method is based on three components: the importance, the dynamics and the interdependence of the university related labour market in relation to the other economic sectors. The importance of the university locations for their respective local economy and in comparison with each other is assessed by an indicator. The dynamic and change of the importance of the different university locations is shown using a shift-share analysis. Both measures can be applied for a classification and spatial clustering of different types of university locations. Additionally, input-output-based employment multipliers are estimated to display the interaction of the university locations with the local economy. The results can be summarised in the identification of three differing regions. The south-east of Lower Saxony is characterised by big, established, well integrated university locations with low dynamics. Adjacent, smaller university locations have difficulties to emerge of the shadows of the dominant locations. In the western part of Lower Saxony can be found small to big university locations with growing importance and continuous development potential. The university locations in the north east are small to medium sized and rather unimportant for the local as well as the total labour market.
Keywords: I23; J48; R12; R15; 330; Regional Input-Output table; employment multiplier; spatial analysis; classification; (in)direct employment effects; universities